A Delphi Consensus Project to Capture Greek Experts’ Opinion on the Position of Triple Therapies in COPD: Why, When and to Whom - Papaioannou AI; Loukides S; Vassilakopoulos T; Tzanakis N; Kostikas K; Hillas G (International Journal of COPD)
Andriana I Papaioannou,1 Stelios Loukides,2 Theodoros Vassilakopoulos,3,4 Nikolaos Tzanakis,5 Konstantinos Kostikas,6 Georgios Hillas,7 The triple therapy for COPD Delphi expert panel members who have contributed to this study.Petros Bakakos1 1, Konstantinos Bartziokas2 2, Afroditi Boutou3 3, Evangelia Fouka4 4, Irini Gerogianni5 5, Athina Gogali6 6, Konstantinos I Gourgoulianis5 5, Paraskevi Katsaounou7 7, Epameinontas Kosmas8 8, Georgios Krommidas9 9, Miltiadis Markatos10 10, Antonios Papaioannou11 11, Konstantinos Porpodis4 4, Nikoleta Rovina1 1, Ioanna Sigala7 7, Paschalis Steiropoulos12 12, Grigorios Stratakos1 1, Dimitrios Toumpanakis13 13, Stavrvos Tryfon14 14, Eleni Tzortzaki15 15, Eleftherios Zervas16 16 On behalf of the Triple Therapy for COPD Delphi Expert Panel1 1st Department of Pulmonary Medicine, National and Kapodistrian University of Athens, Medical School, “Sotiria” Chest Hospital, Athens, Greece; 2 2nd Department of Pulmonary Medicine, National and Kapodistrian University of Athens, Medical School, Attikon’ University Hospital, Athens, Greece; 3Laboratory of Physiology, National and Kapodistrian University of Athens, Medical School, Athens, Greece; 4Critical Care and Pulmonary (2nd) Department, HENRY DUNANT Hospital Center, Athens, Greece; 5Department of Respiratory Medicine, University of Crete Heraklion, Crete, Greece; 6Department of Respiratory Medicine, University of Ioannina, Ioannina, Greece; 7 5th Pulmonary Department, “sotiria” Chest Hospital, Athens, Greece; 1 1st Department of Pulmonary Medicine, National and Kapodistrian University of Athens, Medical School, “Sotiria” Chest Hospital Athens, Greece; 2 2nd Department of Pulmonary Medicine, National and Kapodistrian University of Athens, Medical School, “Attikon” University Hospital Athens, Greece; 3Respiratory Medicine Department, “Hippokration” General hospital of Thessaloniki, Thessaloniki, Greece; 4Pulmonary Department, Aristotle University of Thessaloniki, G. Papanikolaou Hospital, Thessaloniki, Greece; 5Respiratory Medicine Department, Faculty of Medicine, University of Thessaly, Larisa Greece; 6Department of Respiratory Medicine, University of Ioannina, Ioannina, Greece; 7 1st Department of Critical Care Medicine, Evangelismos Hospital, Medical School, National and Kapodistrian University of Athens, Athens, Greece.; 8Department of Pulmonary Medicine “PNOH”, Metropolitan Hospital, Athens, Greece; 9Private Practice, Athens, Greece; 10Private Practice, Chania, Greece; 11Private Practice, Katerini, Greece; 12Department of Respiratory Medicine, Medical School, Democritus University of Thrace, University General Hospital Dragana, Alexandroupolis, Greece; 13 2nd Department of Critical Care Medicine, National and Kapodistrian University of Athens, “Attikon” University Hospital, Athens, Greece; 14Pulmonology Department, “G. Papanikolaou” General Hospital of Thessaloniki, Thessaloniki, Greece.; 15Private Practice, Heraklion Crete, Greece; 16 7th Respiratory Clinic, “Sotiria” Chest Hospital, Athens, GreeceCorrespondence: Andriana I Papaioannou, 1 st Department of Pulmonary Medicine, National and Kapodistrian University of Athens, Medical School, “Sotiria” Chest Hospital Athens, Greece, Tel +30 210 7489671, Email papaioannouandriana@gmail.comBackground: In recent years, COPD treatment has become more personalized considering specific patient’s characteristics.Aim and Methods: We have performed a DELPHI consensus project to assess the level of consensus among Greek experts on the use of triple therapy in COPD as an initial and follow-up treatment. A three-round Delphi online survey was developed. The questionnaire was developed by a 6-member steering committee, included 54 statements, and divided into 3 domains: (A) triple therapy as initial treatment (divided into subdomains examining the impact of exacerbations based on lung function, bronchodilation reversibility and/or blood eosinophil count, smoking, symptoms, and comorbidities), (B) escalation to triple therapy from dual bronchodilation and (C) de-escalation from triple therapy to dual bronchodilation. The survey was funded by AstraZeneca and was hosted and analysed by an independent external company.Results: Consensus was reached in 84.8%, 63% and 80% of statements for domains A, B and C, respectively. Experts agreed that initial treatment with triple therapy is a reasonable option for specific patients, while escalation from dual bronchodilation to triple therapy could be considered, besides frequent exacerbators, also in patients with a history of one moderate exacerbation, mainly in the presence of marked bronchodilator reversibility or high blood eosinophil count. Finally, there was a consensus that de-escalation from triple therapy to dual bronchodilation was inappropriate in patients who had experienced one moderate exacerbation in the previous year.Conclusion: Although consensus was generated in several statements, panelists failed to reach consensus in many aspects of the use of triple therapy, identifying areas for further research.Keywords: COPD, inhaled corticosteroids, exacerbations, dual bronchodilation, triple therapy